Rozwiązane

(1 - 7/9) x (5 1/5 - 7/10)+[ 1- (1/10) do potegi 2] : 9=



Odpowiedź :

(9/9-7/9)*(52/10-7/10)+(100/100-1/100)/9=2/9*45/10+(99/100):9=90/90+(99/100)/9=90/90+11/100=1+0,11=1,11
Kaen27
(1 - 7/9) x (5 1/5 - 7/10)+[ 1- (1/10) do potegi 2] : 9=
2/9x(26/5-7/10)+(1-1/100) :9=
2/9x(52/10-7/10)+99/100:9=
2/9x45/10+99/100x1/9=
1+0,11=1,11
(1 - 7/9) * (5 i 1/5 - 7/10) + [1 - (1/10)²] : 9 =
2/9 * (26/5 - 7/10) + [1 - 1/100] : 9 =
2/9 * (52/10 - 7/10) + 99/100 : 9 =
2/9 * 45/10 + 99/100 : 9 =
90/90 + 99/100 : 9 =
1 + 99/100 * 1/9 =
1 + 99/900 =
1 + 11/100 =
1 i 11/100

pisałam specjalnie każdą linijkę pod spodem, żeby się lepiej odczytywało.
mam nadzieję, że prawidłowy wynik.

Inne Pytanie